Half-correct solutions of elliptical variational inequalities with discontinuous nonlinearities - Pavlenko , V. N. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
The existence of semiregular solutions is established for a certain class of variational inequalities with higher-order differential operators of elliptic type with a discontinuous nonlinearity. The proof is based on a general theorem on abstract variational inequalities with discontinuous operators, obtained by a variational method.